Hidden Treasure : The Impact of Automatic Exchange of Information on Cross-Border Tax Evasion - Beer, Sebastian (IMF Working Papers; Working Paper ;, 2019)
We analyze the impact of exchange of information in tax matters in reducing international tax evasion between 1995 and 2018. Based on bilateral deposit data for 39 reporting countries and more than 200 counterparty jurisdictions, we find that recent automatic exchange of information frameworks reduced foreign-owned deposits in offshore jurisdictions by an average of 25 percent. This effect is statistically significant and, as expected, much larger than the effect of information exchange upon request, which is not significant. Furthermore, to test the sensitivity of our findings, we estimate countries' offshore status and the impact of information exchange simultaneously using a finite mixture model. The results confirm that automatic (and not upon request) exchange of information impacts cross-border deposits in offshore jurisdictions, which are characterized by low income tax rates and strong financial secrecy.